Comparison of efficacy and safety between oral propranolol combined with and without intralesional injection of lauromacrogol for infantile hemangioma - Ma, Fan; Liu, Xiaoliang; Wang, Chuan; Duan, Hongyu; Zhou, Kaiyu; Hu, Fan (Frontiers in Pediatrics, 2024)
The purpose of this study was to compare efficacy and side effects between oral propranolol combined with and without intralesional injection of lauromacrogol for infantile hemangioma(IH).This was a single center randomized controlled prospective study, all participants were firstly diagnosed with IH between August 2022 and January 2023 in our hospital and without any treatment before. Patients were randomized into two groups. PRO group: oral propranolol (2 mg/kg/d) continued for 6 months; PRO+LAU group: oral propranolol(2 mg/kg/d) for 6 months and intralesional injection of lauromacrogol for 2-4 times within 6 months. The dimensions, color, consistency, photographic documentation were well recorded based on Visual Analogue Scale (VAS) before and after starting treatment. According to the treatment response after 6 months, the results were classified into four levels: Grade 1, complete resolution achieved; Grade 2, with ≥50% reduction in size of IH; Grade 3, with ＜50% reduction in size of IH; Grade 4, no response or worsening of IH.Results: A total of 67 patients were involved in the study (17 boys, 50 girls; mean age, 3.6 months, range, 1.1-7.2 months) and randomized to receive oral propranolol combined with or without intralesional injection of lauromacrogol(29 in PRO group, 38 in PRO+LAU group). All patients completed treatment. Eleven patients(37.9%) in PRO group were in Grade 1, 14 patients(48.3%) in Grade 2, 4 patients(13.8%) in Grade 3, compared with these in PRO+LAU group, 11 patients(28.9%) in Grade 1, 24 patients(63.2%) in Grade 2, and 3 patients(7.9%) in Grade 3. No patient was in Grade 4, and no severe side effects were observed in both group. In PRO group, it takes an average of 17.1±5.4 weeks from the start of treatment to cure, and in PRO+LAU group, the average time is 13.7±4.9 weeks.Oral propranolol with intralesional injection of lauromacrogol was a safety treatment strategy for IH. But it was not superior to oral propranolol in final cure rates(P=0.45), moreover, it cannot certainly offer the benefits of shortening the duration of oral drug treatment(P=0.24).